The Associations Between Alexithymic Traits and Trajectories of Depressive and Anxiety Symptoms During Pregnancy among the FinnBrain Birth Cohort Parents - Kirsilä, Santeri (My University, 2022)
Alexithymia is a multidimensional personality construct that literally means “no words for feelings”. Alexithymia can be divided into three dimensions that are difficulty identifying feelings, difficulty describing feelings, and externally oriented thinking style. Especially difficulty identifying feelings and difficulty describing feelings are associated with mental health disorders such as depression and anxiety. Previous research has identified various trajectories for depressive and anxiety symptoms during pregnancy for both mothers and fathers. This study explored associations between three dimensions of alexithymia and trajectories of depressive and anxiety symptoms in a sample of mothers and fathers expecting a child in FinnBrain Birth Cohort data. The study included mothers (N = 1862) and fathers (N = 980) participating to the FinnBrain Birth Cohort Study and having filled out questionnaires of their depressive and anxiety symptoms at three time points across pregnancy and alexithymic traits at 6 months postpartum. Five courses of depressive symptoms and four courses of anxiety were identified in the sample (Korja et al. 2017). High alexithymia scores in difficulty identifying feelings and difficulty describing feelings were associated with the course of consistently high depression and anxiety scores among both mothers and fathers. The study also revealed that high alexithymia scores were strongly associated with rising depressive symptom trajectory during pregnancy in both mothers and fathers. Overall, the results of this study suggest that measuring alexithymia scores may be an important tool in recognizing those in need of extra support during pregnancy.

Aleksitymia on persoonallisuuden piirre, jolla tarkoitetaan heikkoa kosketusta omaan tunne-elämään. Aleksitymia voidaan jakaa kolmeen dimensioon, jotka ovat vaikeus tunnistaa tunteita, vaikeus kuvailla tunteita ja ulkokohtainen ajattelutyyli. Aleksitymian dimensioista erityisesti tunteiden tunnistamisen ja kuvailemisen vaikeuden on todettu olevan yhteydessä mielenterveyshäiriöihin, kuten masennukseen ja ahdistukseen. Aiempi tutkimus on tunnistanut masennusoireille ja ahdistuneisuudelle erilaisia kehityskulkuja lasta odottavien vanhempien raskauden aikana. Tämä tutkimus selvitti yhteyttä aleksitymian eri dimensioiden ja masennuksen sekä ahdistuneisuuden kehityskulkujen välillä lasta odottavilla vanhemmilla FinnBrain kohorttitutkimuksessa kerätyllä aineistolla. Tutkimukseen sisällytettiin äidit (N = 1862) ja isät (N = 980) jotka osallistuivat FinnBrain kohorttitutkimukseen ja olivat täyttäneet kyselylomakkeet masennus- ja ahdistusoireistaan kolmella raskaudenaikaisella mittauspisteellä, sekä aleksitymiaoirekyselyn kuusi kuukautta synnytyksen jälkeen. Otoksessa on tunnistettu viisi masennus- ja neljä ahdistusoireiden kehityskulkua (Korja et al., 2017). Korkeat aleksitymiapisteet tunteiden tunnistamisen vaikeudessa ja tunteiden kuvailemisen vaikeudessa ovat yhteydessä pysyviin korkeisiin masennus- ja ahdistusoireisiin sekä äideillä että isillä. Tutkimus paljasti myös, että korkeat aleksitymiapisteet olivat yhteydessä raskauden aikana nousevien masennuspisteiden kanssa sekä isillä että äideillä. Tämän tutkimuksen tulosten perusteella voidaan vetää johtopäätökset, että aleksitymiapisteiden mittaaminen voisi olla tärkeä tapa tunnistaa raskauden aikana erityistä tukea tarvitsevat lasta odottavat vanhemmat.
Keywords: alexithymia, depression, anxiety, TAS-20, EPDS, SCL-90